Pathways of multiple inflows into a stratified reservoir: Thomson Reservoir, Australia - Marti, Clelia; Mills, R.; Imberger, J. (Elsevier, 2011)
The interaction of multiple inflows entering a reservoir (Thomson Reservoir, Australia). is investigated with a field experiment and. three-dimensional numerical model simulations.The focus of the study is the mixing and transport patterns within the reservoir of the inflowing water.Data from the field experiment showed the existence of multiple inflows intruding horizontally into the reservoir immediately below the thermocline and selectively propagating into the reservoir at a depth determined by the individual density of each inflow. The results serve to show that inflows slot into a stratified reservoir in an orderly fashion, their depth dependent on the separation of inflow densities and reservoir bed, with minimal mixing between intrusions. Inflows thus do not take their nutrient load into the reservoir as a whole, but rather slot their load into an intrusion layer at an appropriate depth. Nutrients brought in via inflows become accessible only when vertical mixing, either directly at the base of the surface layer, or indirectly via the benthic boundary layer flux, transports the intrusion waters into the surface layer. © 2011 Elsevier Ltd.